Preferences and Usage Patterns in Urban Green Spaces: A Case Study of Visitors at Cadika Pramuka Park, Medan City - Kamila Mardhiyyah; Hilma Tamiami Fachrudin; Rahmawaty (International Journal of Architecture and Urbanism, 2026)
Urban green spaces are essential urban infrastructures that support ecological balance, social interaction, and community well-being. This study examines visitor preferences and usage patterns in Cadika Pramuka Park, Medan, following its 2024 revitalization. Using a quantitative approach with 97 respondents, data were collected through structured on-site questionnaires and analyzed using descriptive statistics, Spearman correlations, Chi-square tests, and regression models. The findings show that age, occupation, income, and marital status influence visit duration, timing, and activity types. Accessibility factors, particularly travel time and perceived ease of access, strongly affect visitation frequency and activity choices. Perceptions of facilities also shape active and passive engagement. Overall, the findings emphasize the need for user-centered management that strengthens accessibility, maintains post-revitalization infrastructure, and accommodates diverse demographic needs. The study provides empirical evidence to guide more inclusive, functional, and sustainable urban green-space planning in Medan.